New Fisheries-related data from the Mediterranean Sea (November, 2016) - ANASTASOPOULOU, A.; BIANDOLINO, F.; CHATZISPYROU, A.; HEMIDA, F.; GUIJARRO, B.; KOUSTENI, V.; MYTILINEOU, CH.; PATTOURA, P.; PRATO, E. (Mediterranean Marine Science, 2016)
In this fourth Collective Article, with fisheries-related data from the Mediterranean, we present weight-length relationships for eight deep-sea fish species (Brama brama, Conger conger, Etmopterus spinax, Molva macrophthalma, Mora moro, Pagellus bogaraveo, Phycis blennoides) from the Eastern Ionian Sea; Scyliorhinus canicula from various locations in the Mediterranean Sea and weight-length relationships and condition factor of five Mugilidae species (Liza aurata, Liza saliens, Liza ramada, Mugil cephalus, Chelon labrosus) from a Mediterranean lagoon in the Ionian Sea. Moreover, we present otolith weight, fish length and otolith length relationships of the red mullet (Mullus barbatus) in the Aegean and Ionian Sea and otolith weight relationships in European hake (Merluccius merluccius) from the Greek Seas.